Histone Deacetylase 6 and the Disease Mechanisms of α-Synucleinopathies - Lemos, Miguel; Stefanova, Nadia (Frontiers in Synaptic Neuroscience, 2020)
The abnormal accumulation of α-Synuclein (α-Syn) is a prominent pathological feature in a group of diseases called α-Synucleinopathies, such as Parkinson’s disease, dementia with Lewy bodies (DLB), and multiple system atrophy (MSA). The formation of Lewy bodies (LBs) and glial cytoplasmic inclusions (GCIs) in neurons and oligodendrocytes, respectively, is highly investigated. However, the molecular mechanisms behind α-Syn improper folding and aggregation remain unclear. Histone deacetylase 6 (HDAC6) is a Class II deacetylase, containing two active catalytic domains and a ubiquitin-binding domain. The properties of HDAC6 and its exclusive cytoplasmic localization allow HDAC6 to modulate the microtubule dynamics, acting as a specific α-tubulin deacetylase. Also, HDAC6 can bind ubiquitinated proteins, facilitating the formation of the aggresome, a cellular defense mechanism to cope with higher levels of misfolded proteins. Several studies report that the aggresome shares similarities in size and composition with LBs and GCIs. HDAC6 is found to co-localize with α-Syn in neurons and in oligodendrocytes, together with other aggresome-related proteins. The involvement of HDAC6 in several neurodegenerative diseases is already under discussion, however, the results obtained by modulating HDAC6 activity are not entirely conclusive. The main goal of this review is to summarize and critically discuss previous in vitro and in vivo data regarding the specific role of HDAC6 in the context of α-Syn accumulation and protein aggregation in α-Synucleinopathies.